2010
DOI: 10.1017/s0007114510001571
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, placebo-controlled, cross-over study to establish the bifidogenic effect of a very-long-chain inulin extracted from globe artichoke (Cynara scolymus) in healthy human subjects

Abstract: There is growing interest in the use of inulins as substrates for the selective growth of beneficial gut bacteria such as bifidobacteria and lactobacilli because recent studies have established that their prebiotic effect is linked to several health benefits. In the present study, the impact of a verylong-chain inulin (VLCI), derived from globe artichoke (Cynara scolymus), on the human intestinal microbiota compared with maltodextrin was determined. A double-blind, cross-over study was carried out in thirty-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(157 citation statements)
references
References 61 publications
14
135
1
7
Order By: Relevance
“…Most of the first prebiotics assessed in humans and used commercially were shown to stimulate Lactobacillus and Bifidobacterium specifically, but not pathogens such as certain members of the Clostridia class and Escherichia coli [14][15][16] . As these genera were commonly used as pro biotics, this approach provided a commonal ity between probiotics and prebiotics.…”
Section: Evolution Of the Term Prebioticmentioning
confidence: 99%
“…Most of the first prebiotics assessed in humans and used commercially were shown to stimulate Lactobacillus and Bifidobacterium specifically, but not pathogens such as certain members of the Clostridia class and Escherichia coli [14][15][16] . As these genera were commonly used as pro biotics, this approach provided a commonal ity between probiotics and prebiotics.…”
Section: Evolution Of the Term Prebioticmentioning
confidence: 99%
“…Four trials report inulin supplementation (5-10g/day) to increase faecal Bifidobacterium spp. content relative to control, (Fuller et al, 2007;Kleessen et al, 2007;Ramnani et al, 2010;Costabile et al, 2010). No significant effect of inulin supplementation (5-10g/day) on faecal bacteria content is reported in three trials (Bouhnik et al, 2004;Bouhnik et al, 2007;Calame et al, 2008).…”
Section: Inulinmentioning
confidence: 83%
“…Seven randomised controlled trials in adults were identified that presented evidence on inulin supplementation (doses 5-15g/day) in relation to faecal bacteria content (Bouhnik et al, 2004;Fuller et al, 2007;Kleessen et al, 2007;Bouhnik et al, 2007;Calame et al, 2008;Costabile et al, 2010;Ramnani et al, 2010). The data on measures of faecal bacteria content were insufficiently comparable to allow a meta-analysis.…”
Section: Inulinmentioning
confidence: 99%
“…Inulin also increases the absorption of Ca, has positive effects on lipid metabolism, and has anti-cancer properties (LopezMolina et al, 2005;Sonnante et al, 2007;Lattanzio et al, 2009). Inulin concentrations in globe artichoke roots vary from 30.6% to 36.7% of the dry weight (DW; Costabile et al, 2010), or 18.9% to 36.2% of the DW in the edible portions (Lattanzio et al, 2009). Inflorescence bracts are also a promising source of anthocyanins (Schütz et al, 2006), but the anthocyanin profile seems to 370 FIG.…”
Section: Nutritional and Pharmaceutical Applicationsmentioning
confidence: 99%
“…For example, cardoon flowers have been used traditionally in some areas of Portugal and Spain as a natural source of milk-clotting enzymes for the production of sheep cheese (Verissimo et al, 1995). Thus, Sidrach et al (2005) and Costabile et al (2010) reported that extracts of artichoke flowers could be used as a vegetarian source of the enzymes needed for cheese production. Artichoke has been used traditionally in Italy to make a bitter-type liqueur with allegedly beneficial effects on gastro-intestinal activity, blood clotting time, capillary resistance, and heart activity, in addition to having a neutralising effect on certain toxic substances (Ryder et al, 1983;Ceccarelli et al, 2010).…”
Section: Strategies and Prospects For Alternative Usesmentioning
confidence: 99%